Insights into the production of upgraded biofuels using Mg‐loaded mesoporous ZSM‐5 zeolites. Issue 20 (2nd September 2020) - Sanahuja‐Parejo, Olga; Veses, Alberto; López, José Manuel; Callén, María Soledad; Solsona, Benjamín; Richards, Nia; Taylor, Stuart H.; García, Tomás
Abstract: Bio‐oil catalytic upgrading has been performed using mesoporous Mg‐loaded ZSM‐5. The presence of Mg modifies both textural and acidic properties, which do not only depend on the Mg content (1 and 5 wt. %) but also on the Si/Al ratio of the parent zeolite (25 and 40). Mg impregnation over mesoporous acidic zeolites has been shown to be essential for further deoxygenation of the raw bio‐oil. Thus, remarkable deoxygenation rates have been achieved, exceeding 68 % for a 5 wt. % Mg‐loaded ZSM‐5 (Si/Al=25). For this catalyst, decarboxylation reactions at MgO active sites seem to be predominant, promoting the upgrading of phenols towards the formation of phenolic compounds with lower oxygen content. As in the case of acidic mesoporous ZSM‐5, the formation of aromatics for Mg‐loaded mesoporous ZSM‐5 samples could be mainly related to the promotion of decarbonylation reactions of phenolic compounds over Brønsted acidic sites at the external surface. Interestingly, the presence of strong Lewis acidic sites created by the interaction between (Mg 2+ OH − ) + species and extra framework alumina jointly with the remaining Brønsted acidic sites at the external surface could enhance the formation of aromatics through cascade reactions involving ketonization and further aldol condensation and dehydration reactions. Abstract : Zeolites : Significantly higher deoxygenation rates can be achieved using Mg‐loaded mesoporous ZSM‐5 zeolites compared to parent acidic counterparts. This catalytic performance has been linked to the simultaneous presence of different active sites after Mg impregnation such as MgO nanoparticles, internal strong Lewis acidic sites created by the interaction between (Mg 2+ OH − ) + species and extra framework alumina and remaining Brønsted acidic sites at the external surface.